Interest in Providing Multiple Sclerosis Care and Subspecializing in Multiple Sclerosis Among Neurology Residents - Halpern, Michael T. (The Consortium of Multiple Sclerosis Centers, 2014)
Background: Although detailed knowledge regarding treatment options for multiple sclerosis (MS) patients is largely limited to neurologists, shortages in the neurologist workforce, including MS subspecialists, are predicted. Thus, MS patients may have difficulties in gaining access to appropriate care. No systematic evaluation has yet been performed of the number of neurology residents planning to pursue MS subspecialization. This study identifies factors affecting interest in providing MS patient care or MS subspecialization among current neurology residents. Methods: We randomly selected half of all Accreditation Council of Graduate Medical Education–certified neurology residency programs in the continental United States to receive the neurology resident survey. Completed surveys were received from 218 residents. Results: Residents were significantly more likely to have increased interest in MS care when they participated in MS research, were interested in teaching, and indicated that the “ability to improve patient outcomes and quality of life” was a positive factor influencing their desire to provide MS patient care. Residents who were interested in providing MS care, interested in teaching, and indicated that “research opportunities” was a positive factor for providing MS patient care were significantly more likely to express interest in MS subspecialization. Conclusions: Increasing opportunities to interact with MS patients, learn about MS care, and participate in MS research may increase interest in MS care and subspecialization among neurology residents. Opportunities to educate residents regarding MS patient care may affect residents’ attitudes.